Modernization of Indonesian Islamic Education Critical Study on Madrasah Human Resources Development - Makmur Syukri (Universitas Islam Negeri Sumatera Utara Medan, 2019)
AbstrakThe modernization of Islamic education in Madrasah is an inevitor. The hope of thepeople who are so great to the madrasah to give birth to human beings who havestrong faith, noble morality, knowledge and know-how and reliable skills mustmaterialize from the womb of Madrasah. The sublime ideals would not have beenachieved if the madrasah did not have a qualified human resource in the bearing ofthe generation of gold. This research will reveal the various modernization ofmadrasah blowing in Indonesia, especially in the development of human resourceseducation. The efforts that the government has done aims to renew and improvethe human resources of the Madrasah teachers, for example: the birth of Law No.14 year 2005 about teachers and lecturers, national teachers ' data collection,further education scholarship, Teacher certification, and to add insight andknowledge to the teachers also conducted various workshops, symposium, andeducational seminars.Keywords: Modernization, Islamic education, HR Madrasah